Effect of Teucrium trifidum powder on some meat quality attributes of chevon under refrigerated storage. Issue 5 (May 2022) - Mazhangara, Irene Rumbidzai; Jaja, Ishmael Festus; Chivandi, Eliton
Abstract: We investigated the effect of T. trifidum on the shelf-life and quality of chevon kept for eight days at 4 ± 1 °C in polyethylene pouches. Different powder levels of T. trifidum (0.5 %, 1.0 %, and 2.0 % w/w) and 0.02 % w/w butylated hydroxytoluene (BHT) were used to treat the chevon samples. The T. trifidum and BHT treated chevon was compared to untreated chevon (control). Colour, ferric reducing antioxidant power (FRAP), lactic acid bacteria (LAB) counts, oxidative stability, pH and total viable counts (TVC) were all measured while the samples were in storage. Treatment demonstrated a significant ( P < 0.05 ) influence on pH with chevon preserved with T. trifidum powder (2 %), having a lower pH than the chevon preserved with BHT and the control. The colour of chevon (lightness, redness and yellowness) was shown to differ ( P < 0.05 ) across treatments. The redness (a∗) and yellowness (b∗) reduced as the refrigeration period lengthened ( P < 0.05 ). In contrast, the lightness (L∗) of chevon intensified as the storage period lengthened ( P < 0.05 ). The TBARS considerably reduced ( P < 0.05 ) in samples subjected to T. trifidum powder and BHT, with respect to the untreated sample. There was an increase in the FRAP activity as the amount of T. trifidum powder ( P < 0.05 ) was increased. The FRAP values were shown to be inversely related to the TBARS values, implying that the addition of T. trifidum powder could slow lipid oxidation. In comparison with the control, T. trifidum powder inhibited bacterial growth during storage as measured by a significant reduction in TVC and LAB counts ( P < 0.05 ). It is concluded that, T. trifidum powder has potent antioxidant and antimicrobial activity in refrigerated ground chevon thus can be potentially used to preserve the quality of refrigerator stored ground chevon. Abstract : Consumer health, antioxidant and antimicrobial activity, shelf life, chevon, Teucrium trifidum .